SMALL GROUP DISCUSSION- IMPACT ON STUDENT`S TEST SCORES IN AN UNDERGRADUATE PATHOLOGY COURSE - Sadia Hameed; Tanzeela Khalid; Shazia Aslam et al. (Journal of University Medical & Dental College, 2013)
ABSTRACT Objective: To determine the impact of small group discussion (SGD) on undergraduate learning in Pathology as reflected by student`s test scores. Study design: Quasi Experimental study Context and setting: Fourth year undergraduate students attending pathology course at University Medical and Dental College, Faisalabad in year 2012 Methods: Musculoskeletal system was taught using small group discussions as the main instructional tool. No lectures were taken on this topic before or during the session. A written test comprising of both multiple choice questions (MCQ) and short answer questions (SAQ) was conducted one week after completion of the topic. The results of this test were compared with those of the previous session (historical control), where the same system was taught in a traditional way with lectures. The data was analyzed using SPSS version 17. T-test was used to determine the difference in scores. P-value of <.05 was taken as significant. Results: Students taught by SGD scored significantly higher on musculoskeletal system test as compared to previous batch. Their mean scores on both MCQs and SAQs were significantly higher than students taught by didactic lectures. Conclusion: Small group discussions lead to better cognitive learning as compared to lectures, when compared in terms of test scores.